Hydration and some other properties of polyethylene glycol modified cement products - Singh V.K.; Khatri S.D.; Singh R.K. (My University, 2025)
Effect of polyethylene glycol addition to ordinary Portland cement on its properties like heat of hydration, setting time, compressive and tensile strength has been studied by adding 0.1 to 5.0 percent additive by weight of cement. Corrosion resistance of the resulting product has been tested against sea water and 0.1 and 1.0 N HCI and H2SO4 respectively. Water absorption/open porosity have also been determined and the microstructures examined. It was observed that strength, hardness, toughness and corrosion resistance increase up to 3.0% addition of polyethylene glycol in ordinary Portland cement. The polymeric phase was interspersed in cement causing decrease in water absorption/porosity and also its interaction with hydrating cement caused additional bond formation leading to increase in strength. © 2002 Taylor and Francis Group, LLC.